SOSIALISASI LANJUTAN UNTUK APLIKASI HOSPIBUDGET SEBAGAI ALAT PENGANGGARAN ZERO-BASED BUDGETING BAGI PELAKU HOSPITALITY DAN PARIWISATA DI JAWA BARAT - Sita Deliyana Firmialy; Cahyaningsih Cahyaningsih; Ismaya Adriyanti (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The tourism and hospitality sector are a strategic contributor to regional economic growth; however, many Micro, Small, and Medium Enterprises (MSMEs) in this sector continue to experience challenges in applying effective financial management practices, particularly in adopting digital budgeting systems. Following the development of an Android-based financial management application utilizing the Zero-Based Budgeting (ZBB) approaches, this community service activity focuses on the socialization and practical implementation of the HospiBudget application for hospitality and tourism MSMEs in West Java. The socialization program was designed to address the gap between technological innovation and users’ financial literacy and digital capability. Activities included guided training sessions, hands-on application usage, and discussions on zero-based budgeting concepts tailored to hospitality operations. The program was conducted with MSME participants in the hospitality and tourism sector across several regions in West Java. The results indicate that the socialization significantly enhanced participants’ understanding of ZBB principles, improved their ability to utilize digital budgeting tools, and increased awareness of cost efficiency and cash flow control. This activity demonstrates that application socialization is a critical continuation stage of digital innovation, ensuring that technological solutions such as HospiBudget are effectively adopted and contribute to improved financial governance, business sustainability, and competitiveness of hospitality and tourism MSMEs